Sports Clubs and Populism: Quasi-Experimental Evidence from German Cities - Mona Foertsch; Felix Roesel (Center for Economic Studies and ifo Institute (CESifo), 2023)
Does social capital always promote solidarity and democracy, or are social networks such as sports clubs also vulnerable to populism? We exploit quasi-experimental variation in sports club membership in German cities. Sports clubs are booming in cities with successful soccer teams which pass the promotion threshold for a higher division, but not where teams marginally missed on promotion. Difference-in-differences estimations show that far-right populists enjoy more support in cities with higher sports club membership rates in the wake of marginally promoted soccer teams. The populist momentum is however rather short-living, indicating that sports clubs intensify group polarization but are not a spot of permanent radicalization.
Keywords: D71; D72; Z20; 330; social capital; sports clubs; populism; Gemany